Cost efficiency in China: An empirical analysis of commercial banks during 2013-2018 - Chen, Yujing (2019)
Abstract In this paper, the cost efficiency of commercial banks is evaluated by SFA, a frontier method with random parameters. Among them, there are 147 commercial banks in the study, which mainly analyzed the situation from 2013 to 2018. According to the results of the analysis, it can be found that the average cost efficiency is 95.33%, which is relatively stable, but it would be different due to different years. In addition, the growth of GDP, inflation and the size of banks have no significant impact on the performance of banks. In the six years from 2013 to 2018, the joint-stock commercial banks (JSCBs) are generally more cost-effective than the large state-owned commercial banks (SOCBs).